1979
DOI: 10.1172/jci109473
|View full text |Cite
|
Sign up to set email alerts
|

Hyper Immunoglobulin M Immunodeficiency (Dysgammaglobulinemia)

Abstract: A B S T R A C T The peripheral blood lymphocytes of nine patients with hyper immunoglobulin (Ig)M immunodeficiency were studied in an attempt to define the cellular basis of this disorder. B cells were normal in number but qualitatively abnormal in all patients.Approximately one-half of the B cell consisted of small lymphocytes (7-9 ,um

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(8 citation statements)
references
References 15 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Thus, the limited number of studies of in vitro T cell-proliferative responses to specific antigens have revealed either normal responses to tetanus toxoid or lectins or reduced responses to various antigens, which generally are corrected with booster immunization (11,44,45). In this regard, two of the three patients tested in our series demonstrate normal delayed-type skin test responses without booster immunization (one to tetanus, one to candida and mumps).…”
mentioning
confidence: 66%
“…Thus, the limited number of studies of in vitro T cell-proliferative responses to specific antigens have revealed either normal responses to tetanus toxoid or lectins or reduced responses to various antigens, which generally are corrected with booster immunization (11,44,45). In this regard, two of the three patients tested in our series demonstrate normal delayed-type skin test responses without booster immunization (one to tetanus, one to candida and mumps).…”
mentioning
confidence: 66%
“…Engagement of CD40 on B cells by CD40L or by monoclonal antibody [I 127851 (mAb) results in B cell activation, proliferation, aggregation, and immunoglobulin isotype switching [4,6,[9][10][11][12][13]. Soluble forms of CD40 (sCD40) inhibit T cell-dependent B cell activation and immunoglobulin isotype switching [14].We [15, 161 and others [17-201 have recently reported that a defect in the gene encoding CD40L is responsible for X-linked immunoglobulin deficiency with normal or elevated IgM (X-linked hyper IgM).These patients are unable to synthesize immunoglobulins other than IgM or IgD [21,221, suggesting that interaction between CD40 on B cells and its ligand on activated T cells is critical for immunoglobulin isotype switching. Expression of CD40L in T cells is tightly regulated [23].…”
Section: Introductionmentioning
confidence: 99%
“…Affected males are unduly susceptible to recurrent pyogenic infections, autoimmune diseases, and lymphoproliferative disease. The underlying defect in these patients appears to be an inability to switch from IgM/IgD secretion to the production of other immunoglobulin isotypes, IgG, IgA, or IgE (8,9). We demonstrate that B cells from three males with this syndrome synthesize IgE in response to CD40 mAb plus IL-4 and undergo deletional switch recombination.…”
mentioning
confidence: 80%